A new HLA allele, HLA‐B*08:108, described in two unrelated Spanish individuals. Issue 2 (17th December 2013) - Balas, A.; Sánchez‐Gordo, F.; Gomez‐Zumaquero, J. M.; Prat, I.; Vicario, J. L.
<x xml:space="preserve">Abstract</x> HLA‐B*08:108 shows one nucleotide difference regarding B*08:01:01 at codon 109 (CTC>TTC, L109>F109).